The Influence of Total Quality Recovery in Perceived Enjoyment during Football Specific Training - Okba SELMI; Nejmeddine OUERGHI; Wissam BEN KHALIFA; Fedi AMARA; Anissa BOUASSIDA (Tehran University of Medical Sciences, 2018)
The Influence of Total Quality Recovery in Perceived Enjoyment during Football Specific Training